2014
DOI: 10.1111/gcb.12486
|View full text |Cite
|
Sign up to set email alerts
|

Invasion trajectory of alien trees: the role of introduction pathway and planting history

Abstract: Global change is driving a massive rearrangement of the world's biota. Trajectories of distributional shifts are shaped by species traits, the recipient environment and driving forces with many of the driving forces directly due to human activities. The relative importance of each in determining the distributions of introduced species is poorly understood. We consider 11 Australian Acacia species introduced to South Africa for different reasons (commercial forestry, dune stabilization and ornamentation) to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 68 publications
4
104
0
Order By: Relevance
“…For example, Mainali et al (2015) reported improved prediction performance of ENMs of Parthenium hysterophorus L. (Asteraceae) with the distribution occurrences from both native and invasive ranges. Therefore, it is important to obtain a large volume of occurrences to generate accurate predictions with ENMs (Donaldson et al, 2014;Mainali et al, 2015). Additionally, our study may provide an important theoretical basis for the future prediction of APIs in invasive ranges based on ENMs and aid further studies that study invasion mechanism(s) of APIs on a global scale.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Mainali et al (2015) reported improved prediction performance of ENMs of Parthenium hysterophorus L. (Asteraceae) with the distribution occurrences from both native and invasive ranges. Therefore, it is important to obtain a large volume of occurrences to generate accurate predictions with ENMs (Donaldson et al, 2014;Mainali et al, 2015). Additionally, our study may provide an important theoretical basis for the future prediction of APIs in invasive ranges based on ENMs and aid further studies that study invasion mechanism(s) of APIs on a global scale.…”
Section: Resultsmentioning
confidence: 94%
“…2). Human activities are the main driving force for plant invasion; e.g., human introduction has been reported to disperse invasive plant species over long distances either on footwear or water sports equipment (Brinson and MalvĂĄrez, 2002;Donaldson et al, 2014;Callen and Miller, 2015). Furthermore, hydrological processes of catchments may affect the habitat distribution of species in freshwater biomes (Abell et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The high genetic diversity in urban areas near ports indicates that genetic founder effects have been circumvented. Strong founder effects during ornamental plant invasion can indeed be avoided if the shipped seeds harbour most of the alleles of the source population, and this relatively rich gene pool is used for cultivation and subsequent plantation (Tracy et al, 2011;Donaldson et al, 2014). It remains unclear, however, whether the introductions involved single large seed-shipping events or multiple small seed-trade episodes from the same European area for each of the trade routes.…”
Section: High Genetic Diversity In Urban Bridgehead Populationsmentioning
confidence: 99%
“…parks and public gardens). These urban populations may serve as bridgehead populations (sensu Lombaert et al, 2010;Estoup and Guillemaud, 2010), enabling regular secondary migration to natural areas (Donaldson et al, 2014). The success rate of secondary spread can be expected to further increase if the planted populations originate from genetically distinct native sources, a scenario that is not unlikely in the ornamental plant trade, given that larger trait variation provides a wider basis for artificial selection towards cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation